Analisis Keseimbangan Air pada Daerah Irigasi Matajang Kab. Barru - Sri Nirwana Sari; Mutmainna Syarifuddin; Farouk Maricar; M Agusalim (Fakultas Teknik Universitas Muhammadiyah Parepare, 2025)
Water resources are critical to supporting agriculture, particularly irrigation systems. The Matajang Irrigation Area in Barru Regency, South Sulawesi, is facing issues due to uneven water distribution, climate change, and rising irrigation water demand. The purpose of this study is to evaluate the effectiveness of the present irrigation system and the availability of a consistent discharge to meet the area's irrigation water needs. This study applies a quantitative analytic method, collecting primary data via field surveys and secondary data from relevant institutions, such as rainfall and irrigation land area. Data analysis is conducted using Microsoft Excel to process hydrological data and evaluate water balance. The research results indicate that the water balance in the Matajang irrigation area shows adequate water availability for agriculture, especially during the rainy season, with a dependable flow of Q80 averaging 12.09 l/s (October-March) and 3.34 l/s (April-September).